2019
DOI: 10.1016/j.jcmgh.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Stomach-Type Claudin-18 in Mice Induces Gastric Tumor Formation Independent of H pylori Infection

Abstract: Background & Aims Epithelial cells are joined by tight junctions (TJs) to form a cell sheet. In the stomach, epithelial cell sheet forms an essential barrier against gastric material, including gastric acid. Although the decreased expression of stomach-type claudin-18 ( stCldn18 ), a TJ protein, is generally observed in human gastritis and gastric cancer, its pathological roles are not fully understood. We previously reported that mice lacking stCldn18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…In the current issue of Cellular and Molecular Gastroenterology and Hepatology , a study by Suzuki et al 8 added another important piece to the puzzle. They dissected pathways regulating the transition to metaplasia and then tumor development in young (8 weeks after birth), middle-aged (40 weeks after birth), and aged (>60 weeks after birth) st Cldn18 -KO mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current issue of Cellular and Molecular Gastroenterology and Hepatology , a study by Suzuki et al 8 added another important piece to the puzzle. They dissected pathways regulating the transition to metaplasia and then tumor development in young (8 weeks after birth), middle-aged (40 weeks after birth), and aged (>60 weeks after birth) st Cldn18 -KO mice.…”
mentioning
confidence: 99%
“…They dissected pathways regulating the transition to metaplasia and then tumor development in young (8 weeks after birth), middle-aged (40 weeks after birth), and aged (>60 weeks after birth) st Cldn18 -KO mice. Suzuki et al 8 found that active gastritis in young st Cldn18 -KO mice became chronic active gastritis by the time the mice were middle aged. This transition was accompanied by altered cytokine profiles and increased signal transducer and activator of transcription 3 and nuclear factor-κB signaling.…”
mentioning
confidence: 99%
“…EMT is considered as a response to the combination of extracellular signaling, in which a number of molecules were involved, such as microRNA family. 28,29 To address whether the curcumin-repressed EMT was due to the upregulation of tumor-suppressive miRNAs, a miRNA array containing 90 miRNAs was performed. Therefore, three miRNAs were upregulated, whereas one miRNA was downregulated in SW620 cells after curcumin treatment (Figure 2A-C).…”
Section: Mir-200c Was Induced By Curcuminmentioning
confidence: 99%
“…Helicobacter pylori ( H. pylori ) infection is a well-known risk factor for human gastritis, gastric cancer and inflammation-associated diseases. 1 , 2 , 3 Gastric cancer is a model for inflammation-induced cancer, which is recognized as the third most common cause of cancer related death worldwide. 4 H. pylori which has been christened as a class 1 carcinogen by the World Health Organization (WHO), acquired the shape of an epidemic emerging as a principle cause of gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%